The Role of Emotional Intelligence in Academic Motivation Regulation and Academic Performance among Secondary School Students: Modeling the Mediating Effects of Metacognitive Strategies - Jalali Ghazaani, Zohreh; Abtahi, Masoumeh Sadat; Yazdanpanah, Sadegh (International Journal of Education and Cognitive Sciences, 2026)
Purpose: The present study aimed to investigate the role of emotional intelligence in academic motivation regulation and academic performance among secondary school students, with particular emphasis on the mediating role of metacognitive strategies.Methods and Materials: This applied study employed a descriptive-correlational design using structural equation modeling (SEM). The statistical population consisted of secondary school students in Tehran during the 2024–2025 academic year, from whom 300 participants were selected through multistage cluster sampling. Data were collected using the Schutte Emotional Intelligence Scale, the Metacognitive Awareness Inventory developed by Schraw and Dennison, and an academic motivation regulation scale based on Wolters’ framework. Academic performance was measured using students’ semester grade point averages in core subjects. The validity of the instruments was examined through expert review and confirmatory factor analysis, while reliability was assessed using Cronbach’s alpha and composite reliability coefficients. Data were analyzed using SPSS Version 26 and AMOS Version 24. Pearson correlation analysis, confirmatory factor analysis, structural equation modeling, and bootstrap procedures with 5,000 resamples were employed to test direct and indirect relationships among the study variables.Findings: The results revealed significant positive relationships among emotional intelligence, metacognitive strategies, academic motivation regulation, and academic performance. Emotional intelligence exerted a direct positive effect on metacognitive strategies (β = .48, p < .001) and academic motivation regulation (β = .28, p < .001). Metacognitive strategies positively predicted academic performance (β = .35, p < .001), while academic motivation regulation significantly influenced academic performance (β = .44, p < .001). The structural model demonstrated satisfactory fit indices (χ²/df = 2.14, CFI = .96, TLI = .95, RMSEA = .048, SRMR = .042). Bootstrap analyses further indicated that emotional intelligence had significant indirect effects on academic performance through metacognitive strategies (β = .17, p < .001) and academic motivation regulation (β = .12, p = .005), confirming the mediating roles of these variables.Conclusion: The findings demonstrate that emotional intelligence contributes significantly to students’ academic performance both directly and indirectly through enhanced metacognitive strategy use and more effective academic motivation regulation. These results highlight the interconnected roles of emotional, cognitive, and motivational processes in academic achievement and suggest that educational programs designed to strengthen emotional intelligence and metacognitive competencies may improve students’ motivation, self-regulated learning, and overall academic success.